Aplicación De Los Métodos Científicos De Examen En La Investigación De Pinturas. La Pequeña Madonna De Foligno De Rafael - Rodríguez-Simón, Luis Rodrigo; León-Coloma, Miguel Ángel; López, Vicente del Sol (European Scientific Journal, ESJ, 2018)
The aim of this article is to highlight the importance of Scientific Methods of Examination for the authentication of works of art and, where applicable, attribution to a specific period, school or artist. The results obtained from the technologies applied may provide particularly important data for cataloguing the works in question. Furthermore, they may be compared, in terms of technique and aesthetics, with other similar documents, acquired from paintings of the same author, period or style already identified through historical works. The use of these wide-ranging sets of instruments have been tested on a version of The Madonna of Foligno by Raphael, and very important information on the creative process as well as other highly significant technical data have been gathered to attribute this work to the painter from Urbino.